The autotrophic biorefinery : raw materials from biotechnology - Kourist, Robert; Kourist, Robert; Schmidt, Sandy; Schmidt, Sandy (De Gruyter, 2021)
The depletion of fossil resources and an ever-growing human population create an increasing demand for the development of sustainable processes for the utilization of renewable resources. As autotrophic microorganisms offer numerous metabolic pathways for the fixation of carbon dioxide and the metabolic utilization of light, electricity and inorganic energy donors, they are expected to play a pivotal role in an emerging carbon neutral society. This text-book presents the metabolic principles of autotrophy and current efforts for their utilization in biotechnology, including photoautotrophic, chemolithoautotrophic and electroautotrophic organisms. It outlines how modern molecular biology and process engineering create technologies that allow to use industrial off-gases and inorganic energy for the synthesis of bio-based plastics, materials and other chemical products. The text-book is ideally suited for students in advanced graduate and master courses and offers a reference for PhD students, engineers, chemists, biologists and all with an interests in biotechnology and renewable resources.